The effect of inspiratory parameters after two separate inhalations on the dose emission of theophylline from low and high resistance dry powder inhalers - Mohamad Abadelah; Jumannah Al-Assadi; James Rooney; Hassane Larhrib (Elsevier, 2020)
The dose emission from DPIs can be affected by the inspiratory parameters achieved by the patient as well as the device in-use. Conventional in-vitro dose emission methodology was used, but instead of using inhalation volume (Vin) of 2 or 4 L and peak inhalation flow (PIF) corresponding to 4 kPa, a range of PIFs (28.3, 60, 90 and 120 L min−1) and Vins (0.5, 0.75, 1, 1.5, 2, and 4 L) were used. The formulation was composed of spray dried Theophylline as a model drug with Lactohale® α lactose monohydrate carrier. The formulation was aerosolised using two DPIs; a low resistance Breezhaler® and high resistance Handihaler®. The formulation showed a consistent dose content uniformity with a Coefficient of Variation (CV) of 1.70%. The drug distribution on the surface of the carrier was obvious from the SE micrographs with some drug particles lodged into lactose crevices. The dose emission after the first inhalation (ED1) and total emitted dose (TED) of theophylline increased with PIF and Vin, irrespective of the inhaler device. However, the dose delivered was superior for the Handihaler® compared to Breezhaler®. Drug retention in the capsule and device was high at low PIFs and Vins and reduced after the second inhalation. Therefore, our study supports the recommendations for patients who cannot achieve sufficient PIF and Vin to inhale twice for each dose to ensure the better clinical outcome. Keywords: Peak inhalation flow, Inhalation volume, Theophylline, Handihaler®, Onbrez Breezhaler®